2016
DOI: 10.1039/c6ra20683b
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the adsorption mechanism of glycine in comparison with catechol on cristobalite surface using density functional theory for bio-adhesive materials

Abstract: Amino acid proteins exist in Mussel's adhesive (mefp's) of which glycine has a significant amount. A density functional theory simulation study was performed in a belief that all the proteins in mefp's are responsible for the versatile adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…[26] These two hydroxylated silica surfaces were selected because of their similarity to amorphous silica underwater,w here surface silicon atoms rapidly react with water to form silanols.T he main results from this study were that 1) pyrocatechol showed ah igher affinity (14.15 and 11.65 kcal mol À1 for the (001) and (111) surfaces, respectively) than did water molecules (1.98 and 0.57 kcal mol À1 ), 2) the underlying lattice noticeably affects the adsorption process (pyrocatechol can establish four hydrogen bonds with the (001) lattice but only three with the (111) surface), and 3) irrespective of the surface,catechols prefer to stand upright, that is,n early perpendicular to the surface plane,rather than lay flat. Taking into account this geometry and an average energy of approximately 3.7 kcal mol À1 per bond, it is feasible to consider hydrogen bonding (typically between 2.4 and 6.2 kcal mol À1 ) [27] the most important interaction with amorphous wet silica surfaces.R elated calculations [28] and ab initio molecular dynamic (MD) simulations performed by Ganz and co-workers [29] also supported these results.The authors demonstrated that pyrocatechol displaces preadsorbed water molecules from the substrate by forming competitive hydrogen bonds and the help of dispersion forces from the phenylene ring. [29,30] Finally,b oth DFT and MD calculations noted the torsion capacity of the hydroxy bonds as the origin of the enhanced versatility of catechols to effectively establish hydrogen bonds with different underlying lattices,s ince they can freely rotate with respect to the phenylene ring to find an optimal adsorption geometry.…”
Section: Noncovalent Interactions 211 Hydrogen Bondingmentioning
confidence: 61%
See 1 more Smart Citation
“…[26] These two hydroxylated silica surfaces were selected because of their similarity to amorphous silica underwater,w here surface silicon atoms rapidly react with water to form silanols.T he main results from this study were that 1) pyrocatechol showed ah igher affinity (14.15 and 11.65 kcal mol À1 for the (001) and (111) surfaces, respectively) than did water molecules (1.98 and 0.57 kcal mol À1 ), 2) the underlying lattice noticeably affects the adsorption process (pyrocatechol can establish four hydrogen bonds with the (001) lattice but only three with the (111) surface), and 3) irrespective of the surface,catechols prefer to stand upright, that is,n early perpendicular to the surface plane,rather than lay flat. Taking into account this geometry and an average energy of approximately 3.7 kcal mol À1 per bond, it is feasible to consider hydrogen bonding (typically between 2.4 and 6.2 kcal mol À1 ) [27] the most important interaction with amorphous wet silica surfaces.R elated calculations [28] and ab initio molecular dynamic (MD) simulations performed by Ganz and co-workers [29] also supported these results.The authors demonstrated that pyrocatechol displaces preadsorbed water molecules from the substrate by forming competitive hydrogen bonds and the help of dispersion forces from the phenylene ring. [29,30] Finally,b oth DFT and MD calculations noted the torsion capacity of the hydroxy bonds as the origin of the enhanced versatility of catechols to effectively establish hydrogen bonds with different underlying lattices,s ince they can freely rotate with respect to the phenylene ring to find an optimal adsorption geometry.…”
Section: Noncovalent Interactions 211 Hydrogen Bondingmentioning
confidence: 61%
“…Taking into account this geometry and an average energy of approximately 3.7 kcal mol −1 per bond, it is feasible to consider hydrogen bonding (typically between 2.4 and 6.2 kcal mol −1 ) the most important interaction with amorphous wet silica surfaces. Related calculations and ab initio molecular dynamic (MD) simulations performed by Ganz and co‐workers also supported these results. The authors demonstrated that pyrocatechol displaces preadsorbed water molecules from the substrate by forming competitive hydrogen bonds and the help of dispersion forces from the phenylene ring .…”
Section: The Nature Of the Catechol–surface Interactionmentioning
confidence: 61%
“…Taking into account this geometry and an average energy of approximately 3.7 kcal/mol per bond, it is feasible to consider hydrogen bonding (typically between 2.4-6.2 kcal/mol) [27] the most important interaction with amorphous wet silica surfaces. Interrelated calculations [ 28 ] and ab initio molecular dynamic (MD) simulations performed by Ganz et al [29] also supported these results. The authors demonstrated that pyrocatechol displaces preadsorbed water molecules from the substrate by competitive hydrogen bonds and the help of dispersion forces from the phenylene ring.…”
Section: Hydrogen Bondingmentioning
confidence: 69%
“…We performed the DFT simulations by using the SIESTA package 26 . We drew the structure of the silica surface from the bulk structure of SiO 2 with the tetragonal (P4 1 2 1 ) symmetry having lattice parameters a = b = 4.97 Å and c = 6.93 Å 27–31 . The silica surface was comprised of 16 atomic layers of SiO 2 and a total number of 198 atoms.…”
Section: Methodsmentioning
confidence: 99%
“…The Si and H atoms of the bottom layer of the silica surface were constrained to maintain the bulk structure. We used a large simulation box of ~40 Å in length to remove the art effects of the periodic boundary conditions applied 27–30,32,33 …”
Section: Methodsmentioning
confidence: 99%